1998
DOI: 10.1046/j.1365-2958.1998.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Listeriolysin O: cholesterol inhibits cytolysis but not binding to cellular membranes

Abstract: SummaryListeriolysin O (LLO) binds to cholesterol-containing membranes in which it oligomerizes to form pores. Preincubation of the toxin with cholesterol is known to inhibit haemolysis, whereas the oxidized form of cholesterol has no inhibitor y effect. Using immunoblot analyses and flow cytometry we demonstrate that preincubation with cholesterol does not influence binding of the listeriolysin-cholesterol complex to red blood cells, eukaryotic cells or artificial membranes. Lytic activity of membrane-bound L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 25 publications
7
95
1
Order By: Relevance
“…LLO bound poorly to pure DOPC liposomes, with a slight increase in the the level of binding at pH 6.5 ( Figure 1A) compared to that at pH 8.5 ( Figure 1B). This is in agreement with Jacobs et al (47), who observed weak binding of LLO to phosphatidylcholine liposomes via SDS-PAGE. This unspecific binding was nevertheless negligible compared with binding of LLO to liposomes containing 20% cholesterol (panels C and F of Figure 1 for pH 6.5 and 8.5, respectively).…”
Section: Binding Of Llo To Immobilized Liposomessupporting
confidence: 93%
See 2 more Smart Citations
“…LLO bound poorly to pure DOPC liposomes, with a slight increase in the the level of binding at pH 6.5 ( Figure 1A) compared to that at pH 8.5 ( Figure 1B). This is in agreement with Jacobs et al (47), who observed weak binding of LLO to phosphatidylcholine liposomes via SDS-PAGE. This unspecific binding was nevertheless negligible compared with binding of LLO to liposomes containing 20% cholesterol (panels C and F of Figure 1 for pH 6.5 and 8.5, respectively).…”
Section: Binding Of Llo To Immobilized Liposomessupporting
confidence: 93%
“…Our results thus clearly show that the specificity of LLO for cholesterol is limited to the most exposed hydrophilic part of the sterol molecule. Similar effects of sterol structure on binding or permeabilizing activity were observed for LLO and other CDC (47,53,(63)(64)(65). Our and other results, therefore, show that a specific interaction between cholesterol and CDC exists.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, the bacterium secretes listeriolysin, a poreforming toxin, that allows its efficient escape from the phagolysosome into the cytosol of the infected cell (Kathariou et al, 1987;Cossart et al, 1989;Jacobs et al, 1998;. Within this compartment, L. monocytogenes harnesses components of the host cell cytoskeleton for intracellular motility and cell-to-cell spread (Chakraborty and Wehland 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The CDC from Streptococcus intermedius, intermedilysin (ILY), exhibits an exquisite specificity for human cells (16), suggesting that cholesterol cannot be responsible for membrane recognition by ILY, yet its mechanism still seems sensitive to cholesterol (16). Also, Jacobs et al (17) have shown that the addition of exogenous cholesterol inhibited the activity of the CDC listeriolysin O (LLO) but did not prevent its binding to the membrane. Hence, the mechanism by which cholesterol affects the cytolytic activity of the CDCs remains ambiguous even though the dependence of the CDC cytolytic mechanism on the presence of membrane cholesterol is the defining property of these toxins.…”
mentioning
confidence: 99%